2018
DOI: 10.1002/2017wr022039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stage Measurement Errors on Streamflow Uncertainty

Abstract: Stage measurement errors are generally overlooked when streamflow time series are derived from uncertain rating curves. We introduce an original method for propagating stage uncertainties due to two types of stage measurement errors: (i) errors of the stage read during the gauging and (ii) systematic and nonsystematic (independent) errors of the recorded stage time series. The error models are generic and can be used for any probabilistic rating curve estimation method that provides an ensemble of rating curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 45 publications
(68 reference statements)
1
48
0
3
Order By: Relevance
“…Many studies with several types of sensor have shown that the systematic errors vary in time and depend on the soil water content (Schmitz and Sourell, ; Leib et al, ; Merlin et al, ; Tetlock et al, ). Potential future approaches, as previously used for hydrologic error modelling, include a linear model (Horner et al, ) or a model incorporating independent calibration measurements in a Bayesian analysis framework (Le Coz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies with several types of sensor have shown that the systematic errors vary in time and depend on the soil water content (Schmitz and Sourell, ; Leib et al, ; Merlin et al, ; Tetlock et al, ). Potential future approaches, as previously used for hydrologic error modelling, include a linear model (Horner et al, ) or a model incorporating independent calibration measurements in a Bayesian analysis framework (Le Coz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this type of approach would also require the development of new tools to compare two uncertain flow records, both containing a mixture of systematic and nonsystematic errors. Horner et al () include discussion of this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the image‐based results to existing traditional measurements, that is, floating gauges, reveals deviations between both methods. However, the source of error cannot be clearly identified because traditional gauges entail errors, as well (Horner et al, ).…”
Section: Discussionmentioning
confidence: 99%